From educational to edutainment: issues and challenges of museum public relation in Malaysia - Abdul Manan, Kamaruzzaman (2019)
The museum is an important institution of depositors and "guardians" of national cultural treasures for a country. The museum also plays a role in safeguarding and nurturing the value of a society. Through the museum community can learn and take lessons from events that have taken place. So the success of which was obtained by previous generations can continue to be developed and mistakes that have been made can be prevented from recurring. This paper discusses some of the issues involved in the selected Museums with a view to enhancing the visitor experience. The paper is based on our own experiences and observations from three government and three private Museums in Kuala Lumpur and Selangor. As a result of these experiences, and our interactions with the Museum staff and curators, we have become even more concerned over the museum has been forgotten by society. The current awareness among Malaysian on the importance of Museum somewhat is getting low. Museums often misinterpreted as a storage place of the old stuff that are not relevant to the contemporary lifestyle. This scenario can negatively affect the future of the museum and development of civilization and country. We provide some opinions on this issue, based on our initial experiences. This might give an insight to the museum management of the authority in bringing back the important role of the museum to the people and the country.